Implementasi Faktor-faktor yang Mempengaruhi Nilai Perusahaan - Gesti Putri Wahyudi; Erma Setiawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine empirical evidence of factors that influence firm value. The dependent variable of this research is firm value. Meanwhile, the independent variables of this research are profitability, leverage, capital structure, firm growth, and firm size. This research is quantitative research using secondary data. The sample in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The sampling technique used a purposive sampling method and there were 143 samples that met the criteria during the 5 research periods. The data analysis technique used in this research is a multiple linear regression analysis technique using SPSS 25. The results of this research show that profitability and capital structure have an effect on firm value, while leverage, firm growth, and firm size have no effect on firm value.